Epidemiological and comparative genomic analysis of pathogenic Glaesserella parasuis from livestock agriculture in Shandong, China - Huang, Zetong; Ren, Qinghai; Du, Xusheng; Cao, Shengliang; Li, Yubao (Frontiers in Microbiology, 2025)
Glaesserella parasuis (G. parasuis) is the causative agent of Glässer’s disease, posing a significant economic threat to the livestock agriculture. The present study aimed to investigate the prevalence of G. parasuis in six regions of Shandong Province, China, from June 2023 to November 2024, and to analyze the whole genome of G. parasuis isolates using whole genome sequencing (WGS). This study conducted a comprehensive analysis of the isolates, encompassing antibiotic resistance profiling, virulence gene detection, multilocus sequence typing (MLST), prophage detection, and pan-genome analysis. The prevalence of G. parasuis ranged from 10.8 to 26.5% across different cities in Shandong Province, exhibiting significant seasonal variation (p < 0.01). Among the 45 isolates, serovar 4 accounted for the highest proportion (40%). Antibiotic resistance testing revealed that 55.6% of isolates demonstrated multidrug-resistance (MDR). WGS analysis revealed that 18 distinct sequence types (STs) were identified across the 45 isolates, including 13 newly discovered STs. Notably, all isolates possessed complete prophage sequences. Pan-genome and phylogenetic analysis of 145 G. parasuis strains indicated that G. parasuis possesses an open pan-genome with genetic diversity. In summary, these data enhance our understanding of the molecular characteristics and epidemiological risks of G. parasuis in Shandong Province, China, particularly regarding livestock agriculture.